WISP1 is a novel adipokine linked to inflammation in obesity - Murahovschi, Veronica; Dooley, Steven (Diabetes, 2015)
WISP1 (Wnt1-inducible signaling pathway protein-1, also known as CCN4) is a member of the secreted extracellular matrix-associated proteins of the CCN family and a target gene of the Wingless-type (WNT) signaling pathway. Growing evidence links the WNT signaling pathway to the regulation of adipogenesis and low-grade inflammation in obesity. We aimed to validate WISP1 as a novel adipokine. Human adipocyte differentiation was associated with increased WISP1 expression and secretion. Stimulation of human macrophages with WISP1 led to a proinflammatory response. Circulating WISP1 and WISP1 subcutaneous adipose tissue expression were regulated by weight changes in humans and mice. WISP1 expression in visceral and subcutaneous fat tissue was associated with markers of insulin resistance and inflammation in glucose-tolerant subjects. In patients with nonalcoholic fatty liver disease, we found no correlation among disease activity score, liver fat content, and WISP1 expression. Insulin regulated WISP1 expression in adipocytes in vitro but had no acute effect on WISP1 gene expression in subcutaneous fat tissue in overweight subjects who had undergone hyperinsulinemic clamp experiments. The data suggest that WISP1 may play a role in linking obesity to inflammation and insulin resistance and could be a novel therapeutic target for obesity.